Views of teachers and students about EMI at a Brazilian federal university: implications for language policy - Hendges, Graciela Rabuske; Rodrigues, Gabriel Salinet; Pretto, Amanda de Mendonça (Letras, 2023)
Internationalization is listed as one of the main goals of the Federal University of Santa Maria in its Institutional Development Plan for the period of 2016-2026, and the use of English as a Medium of Instruction (EMI) is pointed out in the document as one of the strategies to achieve this goal. Although it is unofficially known in the institution that graduate classes in some areas are already taught in English, there is no systematic information about these experiences nor an official policy about EMI. The present work attempts to contribute to fill this gap as it reports the main results of an online survey about interests, perspectives and needs in relation to EMI at the university. The survey included professors and students and the data were mainly analyzed quantitatively, in order to establish general patterns within each group and comparisons across groups. The results showed that both professors and students express interest in engaging in EMI classes, but that policy regulation and language support programs are seen as necessary measures to implement it.